Formation of water in crude oil emulsions and microwave-assisted chemical demulsification - Akbari, Sweeta (2016)
With the increasing energy prices and the drive to reduce CO2 emissions, universities and industries are challenged to find new technologies in order to reduce energy consumption, to meet legal requirements on emissions, and for cost reduction and increased quality. Formation of emulsions during oil production and processing is a costly problem, both in terms of chemicals used and production losses. In this thesis, an alternative and cost effective microwave heating technology in demulsification of water-in-crude oil (W/O) emulsions was utilized and investigated. Two different types of Malaysian crude oils namely; heavy and light were mixed together at a volume ratio of (50-50%). The experimental studies began with some important physical and chemical characterizations of crude oil such as density, viscosity, shear rate, shear stress, water content, pour point, interfacial properties, and chemical fractionation of saturates, aromatics, resins, and asphaltenes (SARA), respectively, to provide understanding of fundamental issues such as formation, formulation and breaking of emulsions by chemicals, microwave approaches, and conventional heating. The aim was to obtain the best conditions as well as fundamental understanding of water-in-oil stability, upon which further development on demulsification process could be developed. The stability studies were carried out by analyzing operating conditions such as emulsifier concentration (1.5-2.5vol.%), emulsifier type, and water-oil ratio of (20-80%), (30-70%), and (40-60%). For stability performance test, five emulsifiers were used namely; Span 80, Span 83, Triton X-100, DEA and low Sulphur wax residue (LSWR). Among these, emulsion stabilized by Span 80 was the best for emulsion stability because it produced the emulsions with smallest size of droplets. For emulsion demulsification performance test, three methods were used which are; chemicals, microwave assisted chemicals and conventional method (hot plate). For chemical demulsification test, four demulsifiers with different concentrations (1.5-2.5 vol%) and functional groups were utilized; which are: Octylamine, Hexylamine, Dioctylamine, and Polyethylene Glycol (PEG 600). Among these, Octylamine was found to be the best in separating water and oil from emulsions due to its lower molecular size. For microwave factorial analysis, three factors namely; processing time (1-5 minutes), microwave power (180-540 watt), and demulsifier concentration (1.5-2.5vol.%) using face centered composite design (FCCD) under RSM were employed. The evaluation of microwave demulsification indicated that for microwave heating demulsification the best condition for water separation efficiency was achieved at 3 (minutes), 360 (watt), and 2.50 vol. %. Whereas, the separation efficiency reached at 100 % within 24 hours in emulsion with 40 % water content. The best condition for conventional heating demulsification using FCCD and processing parameters of time (1-5 minutes), temperature (30-160˚C), and demulsifier concentration (1.5-2.5 vol.%) was obtained at 5 minutes, 160˚C, and 1.5 vol.%, where it reached to 96 % within 36 hours in emulsion with 40 % water. The results obtained in this thesis have exposed the capability of microwave-assisted chemical technology in demulsification of W/O emulsions, further works, are nevertheless required to provide a deeper understanding of the mechanisms involved to facilitate the development of an optimum system applicable to the industry.